ASSESSMENT OF THE PHYSICOCHEMICAL PROPERTIES OF SOIL IN FARMLANDS OF BIRNIN YERO, IGABI LOCAL GOVERNMENT AREA, KADUNA STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2024)
Globally, soil degradation is widely recognized as a major agricultural and environmental problem. This study assess the physicochemical properties of soil in farmlands in Birnin Yero, Igabi LGA, Kaduna State. Soil samples were collected from different farmlands and analyzed for particle size (sand, silt, and clay), pH, Organic Carbon (OC), Organic Matter (OM), Exchangeable Acidity (EA), Available phosphate (AP), Calcium (Ca), Magnesium (Mg), Potassium (K), and Sodium (Na). The study revealed that soils of the study area are sandy loam and loamy and the acidic pH indicates the need for soil amendments to improve nutrient availability for plant growth. The medium to low levels of OC, OM, and AP highlight the significance of using soil amendments and focused fertilization techniques to improve soil fertility. Correlations between physicochemical properties demonstrated interrelationships, where EA showed a negative correlation with pH, Mg showed a positive correlation with pH and a negative correlation with EA. K showed a positive correlation with AP and EA. Na showed a positive correlation with Ca. OM had a positive correlation with OM. The percentage of sand in the soils had a negative correlation with OC and OM. Silt soils correlated positively with OC. Then clay soils had a positive correlation with OC and OM. It was concluded that soils from the study area can impact water drainage, nutrient retention, and soil fertility. Furthermore, the physicochemical properties indicate that soil amendments and targeted fertilization strategies should be employed to enhance soil fertility.
Keywords: Physicochemical properties; Farmlands; Soil fertility; Soil degradation; Pollutants; Chemical fertilizers; Manure; Pesticides